Tuberculosis Situation in the Years of the COVID-19 Pandemic – 2020-2021 - I. A. Vasilyeva; V. V. Testov; S. A. Sterlikov (Туберкулез и болезни лёгких, 2022)
The article presents the analysis of changes in preliminary and estimated epidemiological rates: tuberculosis (TB) incidence, TB mortality, and clinical and social structure of new TB cases. It has been found that against the background of continuing improvement of the epidemic situation (reduction of TB incidence and mortality), the clinical structure of TB cases detected in 2020-2021 deteriorated compared to 2015-2019 which was manifested by higher frequency of pulmonary tissue destruction, massive bacterial excretion (by smear), and fibrous cavernous pulmonary TB. The number of TB cases detected post mortem has increased, as well as one-year mortality. These changes indicate low detection of TB cases in 2020. Changes in the incidence of TB/HIV co-infection and the number of new cases with bacterial excretion and multiple drug resistant TB essentially repeat the changes in TB incidence in the resident population during this period.